IMPLEMENTASI METODE USER CENTERED DESIGN (UCD) PADA PERANCANGAN APLIKASI KOPERASI SIMPAN PINJAM BERBASIS ANDROID - Ardi Wijaya; Randi Trio Ardiansyah; Yovi apridiansyah; Diana (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2023)
To make it easier for users to use the application, researchers use the user centered design (UCD) method so that the application is comfortable and easy to use. The advantages of User Centered Design are design-oriented, with a general understanding of the user and in-depth analysis of the user with human characteristics, which is not only a method focus, but also focuses on the specific characteristics and behavior of the target user. By using the UCD model, the application can be used easily but can adjust to the cooperative work system. This research was conducted at the Prosperous Peace Cooperative located in Arga Makmur, North Bengkulu to be precise in Karang Suci Village. And for this research carried out for one month after the seminar and its improvements. The results of this study are based on testing, for the average value of 2 (two) respondents, which is 83% and it is stated that the results of the enterprise architecture design are valid above 50%. And from the results of application feasibility testing using the EA Score Card it can be concluded that the application is declared feasible with a test result of 79%. Which means the application runs well and can be used on Android phones for user applications, and can be used easily by cooperative members to see details of their funds that have been processed by the cooperative.